Pengaruh Disiplin Kerja terhadap Kinerja Karyawan Pada PT. Merek Indah Lestari Medan - Winna Suryani Br Berutu; Ninda Elisa May Saputri Saragih; Rosinta Gultom; Citra Julieta Nahampu; Toman Sony Tambunan (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to examine the influence of work discipline on employee performance at PT. Indah Lestari Medan Brand. This type of research uses a quantitative approach. The data collection technique in this research uses descriptive observations. The instrument used was a questionnaire. With a population of 100 and a sample size of 20. The data analysis technique used is simple regression using SPSS statistical tools. The results of the research found that there is an influence between work discipline on the performance of PT employees. Indah Lestari Medan Brand.